Special Educational Needs, parenting and well-being: contributions from a study performed in Portuguese context. - Felizardo, Sara (2017)
Research on the potential of social support in families of children with Special Educational Needs (SEN) has been maintained that this construct influences dimensions of parental and family functioning, in particular, aspects related to health and well-being of parents. In the same vein, national and international laws give a central role to parents in the defense of educational interests of children, therefore the promotion of quality of life and well-being are key areas in educational and therapeutic contexts. The present study aims i) undertaken a comparative analysis of parents of children with and without SEN in relation to social support and parental well-being (life satisfaction); ii) understanding the relationships between variables of social support and welfare. This is a non-experimental and cross-correlated study and a non probabilistic and convenience sample of 301 parents or caregivers of children with and without SEN. Data were collected in groups of schools and institutions of support for disabled children on the district of Viseu (Portugal). The gathering instruments were the Social Support Questionnaire - short version (Pinheiro & Ferrei.ra, 2001); Life Satisfaction Scale (Neto, Barros & Banos, 1990; Simoes, 1992); Parental Questionnaire (sociodemographic, family and school data). The results show that there arc significant and positive correlations between social support and well-being (in the dimension life satisfaction). The statistics analyzes show the two parents uoups (with and without SEN) have significant differences in welfare and partly on social support (satisfaction with support). Regarding subgroups of parents of children with SEN (cognitive and motor limitations and autism spectrum disorders) we observed significant differences; parents of children with autism showed significantly higher values in social support (availability of support and satisfaction with support) and life satisfaction. The study highlights the predictive value of social support in well-being (life satisfaction).